Development of a tool to evaluate medication management guidance provided to carers of people living with dementia at hospital discharge: a mixed methods study - Danijela Gnjidic; Sarah N Hilmer; Christine Bond; Yun-Hee Jeon; Timothy F Chen; Mouna J Sawan; Melissa Gench (BMJ Open, 2022)
Objective Medication management guidance for carers of people with dementia at hospital discharge is important to prevent medication-related harm during transitions of care. This study aimed to develop a tool to evaluate medication management guidance provided to carers of people with dementia at hospital discharge.Design The tool was developed using mixed methods involving two stages. Stage 1 involved item generation and content validation. Items were based on a previous qualitative study and systematic review. Content validation involved experts and consumers with knowledge or experience of medication management guidance in the acute care setting, and rating each item on importance and relevance. Stage 2 involved conducting cognitive interviews with carers of people with dementia to pretest the tool.Setting For stage 1, experts and consumers from Australia, USA and New Zealand were included. For stage 2, carers of people with dementia were recruited across Australia.Participants 18 experts and consumers participated in round 1 of content validation, and 13 experts and consumers completed round 2. Five carers of people with dementia participated in cognitive interviews.Results The final tool contained 30 items capturing information across five domains: (1) provision of medication management guidance at hospital discharge; (2) carer understanding of medication management guidance provided at discharge; (3) carer engagement in discussing the safe use of medications at discharge; (4) carer preparedness to conduct medication management activities after discharge; and (5) co-ordination of medication management guidance after discharge.Conclusions We developed the first tool to assess medication management guidance provided for carers of people with dementia at hospital discharge. The tool may be useful to inform future research strategies to improve the delivery of medication management guidance at discharge.